DIFFERENT APPROACHES TO TEACHING ENGLISH AS A FOREIGN LANGUAGE TO STUDENTS - Turayeva, Guzal (Журнал иностранных языков и лингвистики, 2021)
English holds a place of status in our country, even after more than six decades since British left India. No native language however has come up to replace English, either as a medium of communication or as an official language. Under the influence of nationalistic feeling and emotional hostility English began to reassert its position. This paper is an overview of the main problems connected with teaching English as a Foreign Language (EFL). It also focuses on the challenges in teaching English.